Information-seeking behaviour of Iranian extension managers and specialists - Gholamreza Pezeshki-Rad; Naser Zamani (Information Research: An International Electronic Journal)
Introduction. We report an investigation designed to explore information-seeking behaviour of extension managers and specialists in Iran, and to identify the factors that correlate with their information-seeking behaviour. Method. A questionnaire was developed to explore information-seeking behaviour of extension managers and specialists. Analysis. Data collected were analyzed using the statistical package for the social sciences (SPSS). Appropriate statistical procedures for description (frequencies, percent, means, and standard deviations) were used. Results. Results showed that the main motivation for seeking job-related information by both public extension managers and specialists was because they were interested in developing their own job-related information. The top three mostly used information sources by extension managers and specialists were Persian books, Persian scientific magazines, and scientific-technical reports. Concerning communication channels, interpersonal communication with colleagues, in-service training courses and scientific-technical conventions were ranked respectively as the three top communication channels used by respondents. There was a negative correlation between managers' years of extension work and their information-seeking behaviour. For specialists, a significant positive correlation was found between years of education and level of job satisfaction with their information-seeking behaviour. Conclusion. Providing valuable information sources, and removing information seeking barriers, can improve information-seeking behaviour of extension specialists and managers.